Drooling in Parkinson's disease: A randomized controlled trial of incobotulinum toxin A and meta-analysis of Botulinum toxins. (September 2016) - Narayanaswami, Pushpa; Geisbush, Thomas; Tarulli, Andrew; Raynor, Elizabeth; Gautam, Shiva; Tarsy, Daniel; Gronseth, Gary
Abstract: Introduction: Botulinum toxins are a therapeutic option for drooling in Parkinson's Disease (PD). The aims of this study were to: 1. evaluate the efficacy of incobotulinum toxin A for drooling in PD. 2. Perform a meta-analysis of studies of Botulinum toxins for drooling in PD. Methods: 1. Primary study: Randomized, double blind, placebo controlled, cross over trial. Incobotulinum toxin (100 units) or saline was injected into the parotid (20 units) and submandibular (30 units) glands. Subjects returned monthly for three evaluations after each injection. Outcome measures were saliva weight and Drooling Frequency and Severity Scale. 2. Systematic review of literature, followed by inverse variance meta-analyses using random effects models. Results: 1. Primary Study: Nine of 10 subjects completed both arms. There was no significant change in the primary outcome of saliva weight one month after injection in the treatment period compared to placebo period (mean difference, gm ± SD: −0.194 ± 0.61, range: −1.28 to 0.97, 95% CI −0.71 to 0.32). Secondary outcomes also did not change. 2. Meta-analysis of six studies demonstrated significant benefit of Botulinum toxin on functional outcomes (effect size, Cohen's d: −1.32, CI −1.86 to −0.78). The other studies used a higher dose of Botulinum toxin A into the parotid glands. Conclusions: This study did not demonstrate efficacy of incobotulinum toxin A for drooling in PD, but lacked precision to exclude moderate benefit. The parotid/submandibular dose-ratio may have influenced results. Studies evaluating higher doses of incobotulinum toxin A into the parotid glands may be useful. Highlights: Incobotulinum toxin A did not help drooling in Parkinson's disease in this study. The study did not have precision to exclude a moderate benefit. The dose of Incobotulinum toxin A in the parotid glands may have influenced results. A meta-analysis of all studies shows that Botulinum toxin is useful for drooling in Parkinson's disease. We discuss reasons for differences in the results of our study and previous studies.